A Cross-Sectional Study: Animal and Vegetable Protein Intake Among Preschool Children - Peni Perdani Juliningrum (NurseLine Journal, 2023)
Protein is one of the macronutrients needed in child growth, which can be obtained from animal and plant foodstuffs. Protein intake gets more attention because energy-protein malnutrition is more common in children under five. Protein nutrition for children must be fulfilled to prevent growth retardation in the next phase. This research aims to establish a profile of preschool children's animal and vegetable protein intake. This type of research is descriptive observational with a cross-sectional design. This research was conducted at Bina Anasprasa Nuris Jember Kindergarden in March 2023. The sample in this study was preschool children aged 3-5 years, totaling 53 people who were taken by purposive sampling. Food consumption data for children was obtained using the 1x24-hour food recall method. Processing and analysis of data using univariate analysis. Preschool girls have more than boys (67.9% and 32.1%). The majority of mothers are not working/housewives (62.3%), while the majority of fathers are self-employed (45.3%). Most families have income above the 2023 Jember UMK (62.3%). Nutritional status with indicators of weight/age, height/age, weight/height of all preschool children has normal, normal, and good nutritional status (100%). Total protein intake increased slightly for boys and families whose income was above the minimum wage. Meanwhile, the intake of vegetable and animal protein sources in preschool children is similar but slightly higher in vegetable protein. Animal protein food ingredients still have high biological value because they contain all essential amino acids compared to vegetable protein. Therefore, preschoolers need to increase their consumption of animal protein food ingredients in their daily diet.